New Form of Economic Development in Highly Urbanized Area and Its Effect on Green Development - Wang, Baohui; Dong, Xiaozhen; Qu, Yanbo; Li, Yan; Ren, Qiuwei; Zheng, Yanfeng; Xu, Zhiwei (Frontiers in Environmental Science, 2022)
The balanced and stable development among economy, society and environment is an important research topic for any region. Given the gap between urban and rural areas, further improving the social security system is a key issue that China urgently needs to solve. This paper uses the autoregressive distributed lag (ARDL) model to evaluate the implementation effect of the two-tier social security system in the Macao Special Administrative Region (MSAR)， and discusses the effect of social security expenditure on green development. The results show that: in the long run, social security expenditure is negatively correlated with regional economic development, but the two-tier social security system has significantly promoted the development of the regional economy. The coupling coordinating relationship between economic growth and green development fluctuated from 2010 to 2020. Compared to economic growth, social security expenditure has a significant negative lag effect on green development. Therefore, the effect of social security on promoting environmental protection and green development needs to be optimized. Through the discussion of the relationship between Macao's social security, economic growth and green development, this study provides relevant practical experience and inspiration for the green development of other region.